Yellowknife Bay, NT -- photograph ... - Seale, Linda N. (University of Alberta Library, 2011)
View SE from Pilots' Monument, Yellowknife, NT across Yellowknife Bay. The ice road to Dettah is visible as a grey line from right to left, beyond the centre group of houseboats, with several vehicles on it. Photograph taken January 2011. ...